2019
DOI: 10.3389/fpsyg.2019.00242
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Human Olfaction: A Meta-Analysis

Abstract: Although the view that women's olfactory abilities outperform men's is taken for granted, some studies involving large samples suggested that male and female olfactory abilities are actually similar. To address this discrepancy, we conducted a meta-analysis of existing studies on olfaction, targeting possible sex differences. The analyzed sample comprised n = 8 848 (5 065 women and 3 783 men) for olfactory threshold (as measured with the Sniffin Sticks Test; SST), n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
172
12
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(243 citation statements)
references
References 82 publications
25
172
12
1
Order By: Relevance
“…Both taste and smell performance then declines after the sixth decade of life [52,53]. Women also appear to outperform men on smell tests, and there is some evidence that women process tastes differently in the brain [54,55]. In this context, it is difficult to draw firm conclusions comparing research from these different fields due to the difference in samples.…”
Section: Discussionmentioning
confidence: 99%
“…Both taste and smell performance then declines after the sixth decade of life [52,53]. Women also appear to outperform men on smell tests, and there is some evidence that women process tastes differently in the brain [54,55]. In this context, it is difficult to draw firm conclusions comparing research from these different fields due to the difference in samples.…”
Section: Discussionmentioning
confidence: 99%
“…3 In other examples, a systematic examination of a panel of 80 common odorants by Cain 4 showed that women were better than men at identifying 74 of the stimuli, and studies by Doty showed that women outperformed men in assigning human body odors to male/female categories. 7 However, reported differences are often small and subject to numerous variables, such as mood, prior experience, age and even socioeconomic status. 7 However, reported differences are often small and subject to numerous variables, such as mood, prior experience, age and even socioeconomic status.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Indeed, the conclusion that females are better than males in many olfactory tasks has been arrived at by most investigators, and a recent meta-analysis confirmed this common belief. 7 However, reported differences are often small and subject to numerous variables, such as mood, prior experience, age and even socioeconomic status. [8][9][10][11] It has also been argued that there have been few studies in humans specifically reporting sex differences in olfactory sensitivity per se, suggesting that in addition to the many variables that can affect performance on olfactory tasks, cognitive or emotional appraisal may play an equally important role.…”
Section: Introductionmentioning
confidence: 99%
“…Prior work has also shown that females often display better performance than males on a variety of olfactory tasks, including both odor naming and odor identification (e.g., Cain, 1982;Cain, Goodspeed, Gent, & Leonard, 1988;€ Oberg, Larsson, & B€ ackman, 2002). However, these effects are small (Sorokowski et al, 2019) and may be due to a number of factors including neural anatomy, gender socialization, hormonal status, other general cognitive differences (e.g., memory consolidation), or an interaction of these factors (Majid, Speed, Croijmans, & Arshamian, 2017). Notably, the bias for female participants to perform better on olfactory tasks runs counter to the pattern of results found in the present study: There was only one female participant in the highest performing group.…”
Section: Discussionmentioning
confidence: 99%